Análisis jurídico de la implementación de una medida alternativa al apremio personal parcial, mediante la utilización del dispositivo de vigilancia electrónico garantizando la seguridad del alimentante - Farfan Ruiz, Nayely Maitee (2024)
The present curricular integration work entitled "Legal analysis of the implementation of an alternative measure to partial personal coercion, through the use of the electronic surveillance device guaranteeing the security of the obligor" has the purpose of demonstrating how the rights of both the obligor and the obligor are violated. of the alimentary with the application of the personal pressure in the matter of food; in addition to the ineffectiveness of this measure. For this, the general study is carried out on everything related to the right to food, the principle of the best interests of the child and the constraints; with the purpose of analyzing the legal problem that arises from the joint implementation of these institutionsin Ecuadorian legislation. All this is framed within our Constitution, the Childhood and Adolescence Code and the General Organic Code of Processes of our country, taking into account that rights are violated, therefore, instead of resorting to personal pressure as only measure, it is suggested to establish an alternative measure such as the electronic surveillance device that guarantees the payment of alimony. The investigation and subsequent analysis, through legal research techniques and methods, seek to define an intermediate point and generate a proposal that serves as a referential instrument for the judge when following the procedure and making decisions in these cases.